Respuesta :
Hello from MrBillDoesMath!
Answer:
4
Discussion:
f(x) = abs (x^3 - 3) =>
f(-1) = abs ( (-1)^3 -3 ) => (-1)^3 = -1
f(-1) = abs( -1 -3 ) => -1 =3 = -4
f(-1) = abs(-4) =>
f(-1) = 4
Thank you,
MrB
The value of the function at f(-1) will be equal to 4.
What is a function?
A function is defined as the expression that set up the relationship between the dependent variable and independent variable.
Given function is
- f(x) = |x³-3|
The value of the function at f(-1) will be calculated as:-
f(x) = | (x³- 3) |
f(-1) = | ( (-1)³-3 ) |
f(-1) = | ( -1 -3 ) |
f(-1) = | (-4) |
f(-1) = 4
Therefore the value of the function at f(-1) will be equal to 4
To know more about function follow
https://brainly.com/question/25638609
#SPJ2